Application of CAD/CAM Technology in Electrochemical Relief Design and Processing of Ceramic Art - Hongyan Li (Journal of Chemistry)
Ceramic relief modeling design and CNC machining programming have a wide range of applications in industrial production and daily life. In view of the actual needs of enterprises, this research studies the CAD simulation technology of ceramic relief and achieves the modeling of other pieces of relief based on the geometric outline of the plane breakthrough. According to geometric relief modeling, bitmap relief modeling, tool path selection, and relief simulation processing, the establishment of a ceramic relief model is realized. Finally, the simulation processing is carried out on the ArtCAM software platform, and reasonable processing parameters are obtained to realize the CNC engraving processing of ceramic relief. The experimental results show that the machining efficiency of the ceramic relief model established in this study is improved by 11.3% and 42.8%, respectively, compared with the two traditional methods, which verifies the correctness and superiority of the designed model.